Basic Investigation on the Electrical Structure Characteristics of 72V Battery Charging Connector - Seo, Sang-Won; Kim, Dong-Jin; Jang, Kyung-Hoon (International Journal of Computational and Experimental Science and Engineering, 2025)
This paper presents a numerical study of a 72-V battery-charging connector, covering electric-field distribution, abnormal 8/20, and transient current during internal short circuits. The connector geometry conforms to KS R 6100-2:2024. While the broader project combines testing and simulation to assess structural and electrical performance, this paper focuses on the simulation methodology and results. Two excitation models are employed: (i) a double-exponential function that reproduces the 8/20 surge waveform specified in KS R 6100-2 and (ii) an exponential rise-decay model that approximates the transient current during an internal short circuit. Electric-field calculations use Maxwell’s equations under a quasi-static assumption, reduced to Poisson’s equation for the scalar potential. Based on the analysis, we propose targeted modifications aD design improvements to the standardized terminal and present an optimized connector model.